Severe necrotic colitis in an adolescent with polypharmacy and high clozapine doses according to his ancestry.: Severa colitis necrotizante en un adolescente con polifarmacia y dosis elevada de clozapina con relación a su origen étnico. - Baptista, Trino; de Leon, José; Guizar, Antonio; Evia, Laura (Investigación Clínica, 2024)
The antipsychotic drug Clozapine (CLZ) is approved for treatment-resistant schizophrenia and reduction in the risk of recurrent suicidal behavior in schizophrenia or schizoaffective disorder. However, it is increasingly used in psychiatry and neurology worldwide in numerous off-label conditions. Clozapine is associated with diverse side effects which require careful monitoring in its use for prevention and treatment. The quality of CLZ use and pharmacovigilance varies considerably among Latin American countries. CLZ-induced gastrointestinal hypomotility (CIGH) is a relevant clinical problem, ranging from innocuous constipation to lethal necrotic colitis. Thus, optimal prevention, early detection, and treatment of CIGH deserves considerable attention. We describe here the case of a 15-year-old Mexican boy diagnosed with Oppositional Defiant- and Attention-Deficit/ Hyperactivity Disorder who developed severe necrotic colitis after nine months of CLZ treatment, leading to permanent ileostomy. We ascribed this unfortunate outcome to careless polypharmacy that did not consider drug-related antimuscarinic activity, deficient clinical monitoring, and lack of attention to ethnicity concerning drug dosing. This case is of educational value for the mental health team in order to promote the proper use of CLZ, which may be life-saving in patients with severe mental disorders.